PENGARUH SOCIAL MEDIA MARKETING TERHADAP BRAND EQUITY (Studi Kasus Pada SMK Permata Harapan) - Silalahi, Rudi Yanto Batara (JURSIMA (Jurnal Sistem Informasi dan Manajemen), 2019)
This study is aimed to determine the effect of social media marketing on brand equity. The population in this study are students of SMK Permata Harapan. this study use non probability sampling methode with purposive sampling technique to obtain a sample of 40 people. The results of this study found social media marketing affect the brand equity of SMK Permata Harapan